1999
DOI: 10.1136/hrt.81.5.470
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of referral of coronary angiography patients in Sweden

Abstract: Objective-To evaluate the appropriateness of referral following coronary angiography in Sweden. Design-Prospective survey and review of medical records. Patients-Consecutive series of 2767 patients who underwent coronary angiography in Sweden between May 1994 and January 1995 and were considered for coronary revascularisation. Main outcome measures-Percentage of patients referred for coronary artery bypass graft surgery (CABG) and percutaneous transluminal coronary angioplasty (PTCA) for indications that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…The prevalence of this syndrome is not well established, but data from registries suggest that about 10% of patients referred for angiography for symptomatic SIHD have coronary anatomy that is not amenable to revascularization. [933][934][935] Other nonpharmacological therapies may be considered in these patients in an effort to improve quality of life.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E411mentioning
confidence: 99%
“…The prevalence of this syndrome is not well established, but data from registries suggest that about 10% of patients referred for angiography for symptomatic SIHD have coronary anatomy that is not amenable to revascularization. [933][934][935] Other nonpharmacological therapies may be considered in these patients in an effort to improve quality of life.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E411mentioning
confidence: 99%
“…Expert panels' ratings of the appropriateness of revascularization in patients with a variety of typical indications, determined according to the RAND-University of California at Los Angeles (UCLA) method, make this judgment explicit, by making it possible to assign patients a score on a scale that ranges from appropriate through uncertain to inappropriate. Studies using this method have shown that overuse [2][3][4][5][6][7][8][9][10][11] of invasive techniques in the management of coronary disease is uncommon, and attention has turned to the issue of underuse. [12][13][14][15][16] Well-designed expert panels can closely reflect the views of practicing physicians, 17 and methods for detecting the underuse of revascularization are highly reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, special attention has been paid to cardiovascular diagnostic procedures due to their clinical importance and high costs. Numerous studies are available that evaluate the contributing factors in physicians' decisions to refer a patient for cardiac catheterization [9][10][11][12] or cardiac computed tomography. 13 The number of single-photon emission computed tomography myocardial perfusion imaging (SPECT-MPI) performed annually has increased in many countries.…”
mentioning
confidence: 99%